Analysis of factors affecting postoperative relapse after bilateral saggital split osteotomy for mandibuler set back. Issue 3 (May 2022) - Himejima, Akio; Nakajima, Masahiro; Fujii, Tomoko; Motohashi, Tomokazu; Shoju, Yuichi; Ohnishi, Yuichi; Okuno, Kentaro; Iseki, Tomio
Abstract: Objective: Postoperative orthodontic treatment after orthognathic surgery is particularly affected by relapse of ≥2 mm. Patients who had undergone surgery were retrospectively reviewed, and factors contributing to relapse were investigated. Methods: The study subjects were 130 patients who underwent bilateral sagittal split ramus osteotomy between January 2016 and December 2017 in our hospital. Lateral cephalometric radiographs were taken preoperatively (T1), immediately postoperatively (T2), and 1 year postoperatively (T3), and the positions of the maxilla and mandible (SNA, SNB), mandibular changes due to surgery [Point B (X, Y), Argo-FH, mandibular plane], hyoid position (MP-H), head position (NSL/CVT, SN-C2C4), and airway space (SPAS, MAS, IAS) were measured. Postoperative changes (T2–T1) and postoperative stability (T3–T2) were assessed, the change in Point B (X) between T3 and T2 was calculated, and those patients in whom this change was <2 mm (Group S) were compared with those in whom it was ≥2 mm (Group R). An unpaired t -test ( p < 0.05) was used for statistical analysis. Results: Complete sets of radiographs were obtained for 42 patients. A comparison of T2–T1 between Group S (n = 33) and Group R (n = 9) found no significant difference in either SNB or Point B (X), but significant differences in MP-H, NSL/CVT, and SN-C2C4 ( p < 0.05). Conclusions: These results showed that postoperative mandibular relapse of ≥2 mm occurred irrespective of the degree of mandibular setback, and it was more likely to occur when surgery had resulted in a greater change in hyoid position.